2020
DOI: 10.1089/cyber.2019.0252
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Facebook Use and Problematic Video Gaming Among Female and Male Gamers

Abstract: The development of modern technologies has facilitated positive functioning in various aspects of everyday life. However, in addition to positive changes, there are also issues related to problematic behavior associated with new technologies and new media, such as problematic Facebook use (PFU) and problematic video gaming (PVG). Therefore, the purpose of the present study was to present the specificity of these problematic behaviors in a group of gamers and to determine their predictors and interrelatedness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 41 publications
7
34
0
1
Order By: Relevance
“…The present study also showed that male gamers had a higher level of PVG and more time spent gaming per week compare to female gamers. This result is in line with previous research [20,146]. Additionally, Hamlen [147] postulated that the increased gaming might lead to increased feelings of success and achievement, which then leads to increased playing time among male gamers.…”
Section: Plos Onesupporting
confidence: 91%
See 4 more Smart Citations
“…The present study also showed that male gamers had a higher level of PVG and more time spent gaming per week compare to female gamers. This result is in line with previous research [20,146]. Additionally, Hamlen [147] postulated that the increased gaming might lead to increased feelings of success and achievement, which then leads to increased playing time among male gamers.…”
Section: Plos Onesupporting
confidence: 91%
“…PFU and PVG were considered as predictors of life satisfaction in the model (see [17,112]). Additionally, the relationship between Facebook hours and PFU as well as game hours and PVG was included (see [20]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations